PENGUATAN KECERDASAN DIGITAL PEMUDA SEBAGAI BENTUK KETERLIBATAN DALAM TOTAL DIPLOMASI INDONESIA - Christy Damayanti; Andika Drajat Murdani (Lembaga Penelitian dan Pengabdian Masyarakat, 2020)
The digital age encourages the flow of information to move quickly and shift the pattern of international relations. This has influenced the development of the total diplomacy scheme in supporting the achievement of Indonesia's diplomacy goals. In this program, we take international relations students of Slamet Riyadi University as activity partners.International Relations students should be able to engage in total diplomacy positively. They will be provided with digital intelligence according to the positive character of the nation is needed, so that they are able to contribute in growing Indonesia's positive image in the international eyes. This community service program would like to support Indonesia's efforts to collaborate digital media in a total diplomacy scheme with student youth agents, through